1998
DOI: 10.1146/annurev.ento.43.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Insect Performance on Experimentally Stressed Woody Plants: A Meta-Analysis

Abstract: In this review, we test the hypothesis that abiotic stress increases the suitability of plants as food for herbivores. We conducted a meta-analysis that included 70 experimental studies in which insect performance was measured on woody plants subjected to water stress, pollution, and/or shading. Overall, plant stress had no significant effect on insect growth rate, fecundity, survival, or colonization density. We found great variation, however, in the magnitude and direction of insect responses among studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
360
4
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(389 citation statements)
references
References 104 publications
20
360
4
5
Order By: Relevance
“…3). This finding is in line with the results of a meta-analysis of 147 studies involving carbon-based defence compounds in a variety of woody species (Koricheva et al 1998). These authors reported overwhelming evidence that high nitrogen fertilisers led to a decrease in foliar concentrations of a range of carbon-based secondary compounds.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3). This finding is in line with the results of a meta-analysis of 147 studies involving carbon-based defence compounds in a variety of woody species (Koricheva et al 1998). These authors reported overwhelming evidence that high nitrogen fertilisers led to a decrease in foliar concentrations of a range of carbon-based secondary compounds.…”
Section: Discussionsupporting
confidence: 84%
“…3b) is at odds with the findings of several other studies of both total phenolics and condensed tannins (e.g. Waterman et al 1984, Hartley et al 1995Lawler et al 1997;Koricheva et al 1998). These studies found a decrease in carbon-based compounds, which they attributed to the lower overall energy and carbon supply from photosynthesis in shaded plants.…”
Section: Discussionmentioning
confidence: 84%
“…Actually, it can be assumed that most studies published in recent decades did not have the aim of testing the generality of a positive interaction between drought and pathogens, such as the Plant stress hypothesis, i.e. that abiotic stress increases the suitability of plants as food for herbivores, often referred to by entomologists [103]. Rather, experimental studies mostly focused on some pathogens for which circumstantial evidence linking drought and disease in natural conditions had previously been reported, with the aim to bring experimental support and some insights to our understanding of the processes involved [173,175].…”
Section: Disease Typesmentioning
confidence: 99%
“…Many reviews have looked at the direct or indirect impacts of drought on insects at the individual level [45,48,50,53,60]. However, whether responses at this level will translate into effects at the population or community level will depend on the net result of complex interactions.…”
Section: Introductionmentioning
confidence: 99%